2020
DOI: 10.1186/s13036-020-0225-9
|View full text |Cite
|
Sign up to set email alerts
|

Signature mRNA markers in extracellular vesicles for the accurate diagnosis of colorectal cancer

Abstract: Background With the increasing incidence of colorectal cancer (CRC), its accurate diagnosis is critical and in high demand. However, conventional methods are not ideal due to invasiveness and low accuracy. Herein, we aimed to identify efficient CRC mRNA markers in a non-invasive manner using CRC-derived extracellular vesicles (EVs). The expression levels of EV mRNAs from cancer cell lines were compared with those of a normal cell line using quantitative polymerase chain reaction. Eight markers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…Studies in cell lines, as previously shown, have provided insight into possible biomarkers, but these results still have to be confirmed in patients to ascertain the real potential of these molecules as biomarkers. As an example, Cha et al (2020) selected a total of 12 mRNAs that were differentially expressed in EVs from 4 colorectal cancer cell lines, and through a series of comparisons, identified that the combination of only two of these mRNAs— CD133 and VEGF —was able to distinguish colorectal cancer patients from healthy controls. However, the combination of these two mRNAs achieved 100% sensitivity with extremely high specificity and accuracy.…”
Section: Therapeuticsmentioning
confidence: 99%
“…Studies in cell lines, as previously shown, have provided insight into possible biomarkers, but these results still have to be confirmed in patients to ascertain the real potential of these molecules as biomarkers. As an example, Cha et al (2020) selected a total of 12 mRNAs that were differentially expressed in EVs from 4 colorectal cancer cell lines, and through a series of comparisons, identified that the combination of only two of these mRNAs— CD133 and VEGF —was able to distinguish colorectal cancer patients from healthy controls. However, the combination of these two mRNAs achieved 100% sensitivity with extremely high specificity and accuracy.…”
Section: Therapeuticsmentioning
confidence: 99%
“…Cha et al [ 143 ] evaluated eight mRNA markers (MYC, VEGF, CDX2, CD133, CEA, CK19, EpCAM, and CD24) extracted from plasma EVs. Of the eight mRNAs, the combination of VEGF and CD133 showed statistically significant differences between healthy and CRC, and obtained an AUC of 0.96 with 100% sensitivity and 80% specificity in discriminating between the two groups.…”
Section: New Testsmentioning
confidence: 99%
“…Although current molecular biomarkers have a good performance, these perform correctly only within a small population of patients at specific CRC stages and with specific molecular characteristics, rendering them insufficient for a wide-range CRC diagnosis [ 20 , 94 ]. Thus, the research community keeps moving forward to develop new and more accessible molecular biomarkers that can be found more abundantly and with a broader diagnosis range, capable of diagnosing most CRC stages despite its heterogeneity, since CRC early diagnosis is critical for survival and is currently in high demand [ 95 , 96 ].…”
Section: Current Clinical Molecular Biomarkers For Crcmentioning
confidence: 99%